Behavioural responses of a large, heat‐sensitive mammal to climatic variation at multiple spatial scales. Issue 3 (4th January 2023) - Verzuh, Tana L.; Rogers, Savannah A.; Mathewson, Paul D.; May, Alex; Porter, Warren P.; Class, Corey; Knox, Lee; Cufaude, Teal; Hall, L. Embere; Long, Ryan A.; Monteith, Kevin L.
Abstract: Climate warming creates energetic challenges for endothermic species by increasing metabolic and hydric costs of thermoregulation. Although endotherms can invoke an array of behavioural and physiological strategies for maintaining homeostasis, the relative effectiveness of those strategies in a climate that is becoming both warmer and drier is not well understood. In accordance with the heat dissipation limit theory which suggests that allocation of energy to growth and reproduction by endotherms is constrained by the ability to dissipate heat, we expected that patterns of habitat use by large, heat‐sensitive mammals across multiple scales are critical for behavioural thermoregulation during periods of potential heat stress and that they must invest a large portion of time to maintain heat balance. To test our predictions, we evaluated mechanisms underpinning the effectiveness of bed sites for ameliorating daytime heat loads and potential heat stress across the landscape while accounting for other factors known to affect behaviour. We integrated detailed data on microclimate and animal attributes of moose Alces alces, into a biophysical model to quantify costs of thermoregulation at fine and coarse spatial scales. During summer, moose spent an average of 67.8% of daylight hours bedded, and selected bed sites and home ranges that reduced risk of experiencing heat stress. For most of the day, shade could effectively mitigate the risk of experiencing heat stress up to 10°C, but at warmer temperatures (up to 20°C) wet soil was necessary to maintain homeostasis via conductive heat loss. Consistent selection across spatial scales for locations that reduced heat load underscores the importance of the thermal environment as a driver of behaviour in this heat‐sensitive mammal. Moose in North America have long been characterized as riparian‐obligate species because of their dependence on woody plant species for food. Nevertheless, the importance of dissipating endogenous heat loads conductively through wet soil suggests riparian habitats also are critical thermal refuges for moose. Such refuges may be especially important in the face of a warming climate in which both high environmental temperatures and drier conditions will likely exacerbate limits to heat dissipation, especially for large, heat‐sensitive animals. Abstract : Using a biophysical model, moose metabolic rates were predicted at multiple spatial scales and incorporated as heat risk factors in habitat selection models. Accounting for other factors known to influence habitat selection, moose selected for bed sites and home ranges that conferred a lower risk of overheating than available habitat.